Pengaruh Net Profit Margin, Leverage, Return On Assets, Return On Equity, dan Kebijakan Deviden Terhadap Nilai Perusahaan Sektor Manufaktur Yang Terdaftar di BEI Periode 2020-2022 - Ardi Ibrahim; Yola Andesta Valenty; Sutarni Sutarni (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
This research aims to empirically test the influence of NPM, leverage, ROA, ROE and dividend policy on company value, namely in manufacturing sector companies listed on the BEI from 2020 to 2022. This research uses quantitative descriptive methods, and the data used in This research is: research with secondary data sources by collecting data from the official website of the Indonesian Stock Exchange as well. The data population used in this research is 239 companies listed on the IDX. Using a purposive sampling method, this research used a sample of 45 manufacturing sector companies registered in the 2020-2022 period. Tests are carried out to find out whether company value can be measured by various factors in this context. This research uses the PLS 3.0 application to test the influence of net profit margin, leverage, return on assets, return on equity and dividend policy on company value. The results of this research show that NPM has a positive and not significant effect, Leverage has a positive and not significant effect, ROA has a negative and not significant effect, ROE has a significant positive effect and dividend policy has a positive and not significant effect on share value. manufacturing sector companies listed on the IDX for the 2020-2020 period